2019
DOI: 10.3390/ijms20112825
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of GD3 Synthase in Mice Resulting in the Attenuation of Bone Loss with Aging

Abstract: Gangliosides are widely expressed in almost all tissues and cells and are also considered to be essential in the development and maintenance of various organs and tissues. However, little is known about their roles in bone metabolism. In this study, we investigated the effects of genetic deletion of ganglioside D3 (GD3) synthase, which is responsible for the generation of all b-series gangliosides, on bone metabolism. Although b-series gangliosides were not expressed in osteoblasts, these gangliosides were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…These sialosylated molecules are involved in many physiological processes, including growth, differentiation, migration and apoptosis through modulation of both cell signalling processes and cell-to-cell and cell-to-matrix interactions [3][4][5][6]. A recent report provides evidence of the role of GD3 synthase (ST8Sia-I) in bone metabolism in animals and suggests that altered ganglioside metabolism is associated with this bone loss during aging [7]. Alterations of ganglioside composition have been shown to occur upon transformation and upon cellular differentiation [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sialosylated molecules are involved in many physiological processes, including growth, differentiation, migration and apoptosis through modulation of both cell signalling processes and cell-to-cell and cell-to-matrix interactions [3][4][5][6]. A recent report provides evidence of the role of GD3 synthase (ST8Sia-I) in bone metabolism in animals and suggests that altered ganglioside metabolism is associated with this bone loss during aging [7]. Alterations of ganglioside composition have been shown to occur upon transformation and upon cellular differentiation [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a new role for sialidase NEU1 on the regulation of TLR4 was demonstrated [28]. However, there is little information about the presence of endogenous ecto-ST8-SiaI in macrophages [7].…”
Section: Introductionmentioning
confidence: 99%
“…Glycosphingolipids are divided into three main series, i.e., ganglioside-series, globo-series, and lacto/neolacto-series. Of these, gangliosides have been reported to be involved in bone metabolism [5,6,7,8,9]. For instance, it was reported that a-series ganglioside GD1a and GM1 promote osteoblastic differentiation of bone marrow mesenchymal stem cells (MSCs) and tendon stem cells [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was reported that a-series ganglioside GD1a and GM1 promote osteoblastic differentiation of bone marrow mesenchymal stem cells (MSCs) and tendon stem cells [5,6,7,8]. Recently, we demonstrated that a lack of GD3 synthase, which is responsible for the generation of all b-series gangliosides, in mice results in the attenuation of bone loss with aging [9]. However, there have been no reports on the presence or absence of expression of globo-series glycosphingolipids in osteoblasts and osteoclasts, and the roles of these glycosphingolipids in bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, little is known about roles of GD3 synthase and its products in bone metabolism. Yo et al clearly demonstrated implication of gangliosides in bone resorption using GD3 synthase-KO mice [ 24 ] as a novel function.…”
mentioning
confidence: 99%